Banking system of cyprus - Phylaktis, Kate (London, 1995)
The book provides a comprehensive study of the banking system in Cyprus from the time that the first bank was founded on the island in 1864. It presents the history of banks and co-operative societies from primary sources and discusses its impressive expansion in the years following independence in 1960. It examines the potential of the offshore banking sector, and the likely effects of financial deregulation and the adoption of the EEC Banking Directives on the future development of the banking system.
Keywords: Banks and banking - Cyprus